Eksternalisasi Kompetensi Guru Terhadap Akhlak Peserta Didik - Sumiati, Cucu; Dr, Wawan; Juanda, Ayi (THORIQOTUNA: Jurnal Pendidikan Islam, 2024)
This study aims to analyze and explain how the effect of Islamic Religious education teacher competence on Student Morals. The type of research used in this research is quantitative research, all actions taken are an effort to find out and measure "The Influence of the Competence of Islamic Religious Education Teachers on the Morals of Students". Data collection techniques used include: observation, questionnaires, and interviews. As well as techniques analysis of the data used are: Correlation analysis correlation analysis with Rank Spearman. Based on the results of the study it was stated that the competence of Islamic religious education teachers had a very influential correlation with the morals of students. With the result that the rs value of 0.51 is in the moderate classification, because it is in the interval 0.41 - 0.60. This means that the competence of Islamic religious education teachers has an adequate correlation with the morals of students in grades IV, V and VI at SDN Cidahu. The degree of determination obtained on the competency indicator of Islamic religious education teachers on the morals of students at Cidahu Elementary School is 26.01%, while the remaining 73.99% is influenced by other factors that contribute to variable Y. After calculating it turns out that thitung is 3.56 while based on the significance level (∝= 0,10) and obtained in list t (0.9) (30) is 1.308. Thus if t hitung ≥ t tabel then \mathrm Ha is accepted and HO is rejected. The results above show that there is a positive and significant influence between the competence of Islamic religious education teachers on the morals of students at SDN Cidahu